Evidence for lateral premotor and parietal overactivity in Parkinson's disease during sequential and bimanual movements. A PET study. - Samuel, M; Ceballos-Baumann, A; Blin, J; Uema, T; Boecker, H; Passingham, R; Brooks, D (1997)
Patients with Parkinson's disease have great difficulty in performing sequential and bimanual movements. We used H2(15)O PET to study the regional cerebral blood flow associated with performance of sequential finger movements made unimanually and bimanually in a group of Parkinson's disease patients and a group of control volunteers. In controls, sequential finger movements led to activation of the contralateral motor cortex and inferior parietal cortex (Brodmann area 40), the lateral premotor cortex and bilateral supplementary motor area. No prefrontal activation was seen. Sequential finger movements in the Parkinson's disease group were associated with a similar pattern of activation but there was relative impairment of activation in the mesial frontal and prefrontal areas. A novel finding was the presence of relative overactivity in the lateral premotor and inferolateral parietal regions. We conclude that in Parkinson's disease there is a switch from the use of striato-mesial frontal to parietal-lateral premotor circuits in order to facilitate performance of complex finger movements.